Peran Minat sebagai Variabel Intervening pada Pengaruh Religiusitas, Kepercayaan dan Fitur Layanan terhadap Keputusan Penggunaan Internet Banking (Studi Nasabah Bank Jateng Syariah) - Wiji Rahayu Setyoningsih; Qi Mangku Bahjahtulloh (Universitas Muhammadiyah Surabaya, 2023)
Abstract The purpose of this study is to test and analyze the influence of Religiosity, Trust and Service Features on the Decision to Use Internet Banking Bank Jateng Syariah with interest as an intervening variable. The sampling technique used in this study was random sampling involving 316 respondents. The research instrument used a questionnaire and this research was carried out quantitatively through regression analysis and path analysis. The results of the analysis show that religiosity, trust and service features have a positive and significant effect on the decision to use Bank Jateng Syariah Internet Banking. Furthermore, interest not mediation the relationship between religion, beliefs and service features on decisions to use internet banking at Bank Jateng Syariah. Keywords: Religiosity, Trust, Service Features, Interests, Decisions